Buffalo Agribusiness and Rural Household Income: Mediating Effects of Farmer Characteristics in Lindu District, Indonesia - Sayekti Handayani; Suparmin Fathan; Haerani Maksum; Afandi Afandi; Hasnadia Hasnadia; Siti R. Machieu; Ramlan Mustapa; Safriyanto Dako; Delvi Suleman (Jambura Agribusiness Journal, 2026)
Buffalo farming is an important part of agribusiness activities that play a role in supporting the economy of rural livestock families. Buffalo farming contributes to family income beside providing a source of food and labor. Buffalo farming agribusiness needs to be continuously optimized with the hope of optimizing the capital and competency aspects of farmers in order to optimize the economy and family income. The study aims to determine (1) the contribution of buffalo agribusiness to family income, and (2) analyze the influence of land area (capital factor) and farmer experience (competence) on family income through livestock agribusiness. The research used a Mixed Method Sequential Explanatory approach. The data source in this study was primary data from questionnaires distributed to 85 livestock farmers, followed by interviews, observation, and documentation. Data analysis used descriptive statistics, path analysis, and Sobel test. Research results showed that Buffalo agribusiness contributed an average of 44.09% to family income, with the lowest contribution of 2.23% and the highest 98.48%. Path analysis showed that land area and livestock farmer experience did not have a significant direct effect on family income, with land area being more influential than farmer experience. However, the Sobel test showed that land area and livestock farmer experience had a positive and significant effect when using buffalo agribusiness income as a mediating variable, farmer experience was the most dominant influence in indirect effect. Income from buffalo agribusiness plays a strategic role in increasing the influence of capital and livestock farmer competency on household economic well-being. These results emphasize the importance of strengthening an integrated, land-based, and experience-based buffalo agribusiness system, policy interventions in the form of capacity-building training for farmers, optimal utilization of land resources, and institutional support to enable buffalo agribusiness to become a primary pillar in strengthening family economic resilience.